Serum C-reactive protein in food protein-induced enterocolitis syndrome versus food protein-induced proctocolitis in Japan - Kimura, Mitsuaki; Shimomura, Masaki; Morishita, Hideaki; Meguro, Takaaki; Seto, Shiro (Pediatrics international, 2016)
Background Some infants with food protein‐induced enterocolitis syndrome (FPIES) have increased serum C‐reactive protein (CRP) and fever in Japan. The aim of this study was therefore to clarify and compare the incidence of this in patients with FPIES versus patients with food protein‐induced proctocolitis (FPIP). Methods One hundred and sixteen infants with non‐IgE‐mediated gastrointestinal food allergies were enrolled in this study and classified into three phenotypes: FPIES presenting with vomiting and/or diarrhea (n = 47); FPIP with bloody stool alone (n =19); and the mixed phenotype (MP), bloody stool with vomiting and/or diarrhea (n = 50). Results Serum CRP was increased in 55.3% of the FPIES group, similar to that in the MP group (54.0%), and significantly higher than in the FPIP group (15.8%; P < 0.01). Fever was observed in 29.8% of the FPIES group, significantly higher than in the MP group (8.0%; P < 0.01) and in the FPIP group (0%; P < 0.05). Patients with fever had significantly higher serum CRP than patients without fever (median, 12.8 vs <0.2 mg/dL, P < 0.00001). Conclusions Serum CRP was significantly higher in the FPIES group than in the FPIP group. This suggests that serum CRP is a useful marker for differentiating the pathogenesis of FPIES from FPIP. From the perspective of serum CRP, the pathology of the intestinal inflammation in MP subjects is suggested to be similar to that of FPIES.